An Economic Theory of Sexual Exchanges and Human Capital - Elias Carroni; Marina Della Giusta; Davide Dragone (Institute of Labor Economics (IZA), 2025)
We develop a rational choice model of sexual exchange that unifies marriage and paid sex, explaining two key facts: the gendered segregation of sex markets and the decline in sexual activity and fertility. Individuals choose whether to engage in paid or unpaid sex based on income, human capital, and social norms. Gendered patterns emerge endogenously from the asymmetric distributions of these traits. The model also shows how the rise of digital sex reduces the cost of supplying sex, increases market participation, and reallocates time away from unpaid intimacy–leading to lower fertility even without biological constraints.
Keywords: 10; J10; J12; J16; J22; J24; 330; sexual exchanges; fertility; gender norms; human capital; sex buyer; sex work